Layers of authenticity: Tracing multicultural narratives in the goethe-institut building as a symbol of urban branding in yangon - Win, May Thinzar (The Journal of City: Branding and Authenticity, 2025)
Background: This study investigates the Goethe-Institut building in Yangon, Myanmar, highlighting its significance as a case of adaptive reuse and heritage conservation. Constructed in the 1920s during British colonial rule, the building showcases a blend of architectural styles, merging colonial engineering with Burmese, Chinese, and Indian design elements. Over the years, it has transitioned from a private residence to a revolutionary headquarters, an art school, and now serves as a cultural hub. Methods: This study examines the Goethe-Institut building in Yangon, Myanmar, through site observations, historical analysis, and a literature review, focusing on its architectural significance and role in heritage conservation. Findings: The research delves into the building's historical evolution and architectural features while addressing the challenges of adaptive reuse within urban heritage conservation. It emphasizes how these strategies have preserved historical authenticity while meeting contemporary needs and sustainability goals. Key elements such as high ceilings, wide verandas, and intricate carvings are analyzed for their cultural significance. By comparing similar projects across Southeast Asia, the study illustrates the potential of heritage conservation to enhance cultural identity and community engagement. It argues that the Goethe-Institut exemplifies the transformative power of adaptive reuse in preserving architectural heritage, offering insights for sustainable urban development and postcolonial narratives. Conclusion: The findings underscore the importance of integrating historical context with modern functionality to foster resilience in urban environments. Novelty/Originality of this article: This study provides a unique contribution by analyzing the Goethe-Institut building in Yangon as a case of adaptive reuse, highlighting its role in preserving architectural heritage while addressing contemporary sustainability challenges, and offering comparative insights from similar projects across Southeast Asia.